Traffic Demand Forecasting for Port Services - Jugović, Alen; Hess, Svjetlana; Poletan Jugović, Tanja (Promet - Traffic&Transportation, 2012)
Successful management of any sea port depends primarily on the harmonisation of transport supply and demand, whereas their incompatibility leads to a number of problems. The port, i.e. its management, through its operation and part of port policy may affect the planning of the construction or modernization of its port facilities. In doing so, the specified planning requires forecasting and quantification of the needs for infrastructural services of specified port, i.e. assessment of traffic demand. Accordingly, the basic problem of research in this paper is forecasting of traffic demand for the port services by applying the appropriate forecasting methods. In order to find ways of solving concrete problems in the port operations the methods for traffic demand forecasting are set by applying the methodology and the presentation of the application of economic forecasting methods. The selected methods of demand forecasting for port services in demand are illustrated and tested on the example of the Croatian largest cargo port, the Port of Rijeka.KEY WORDS: planning, forecasting, traffic demand, commodity flows, port capacity